Dra’ Abu el-Naga, Ägypten. Die Särge des Imeni und der Geheset – Textzeugen an der Schwelle zwischen Sargtexten und Totenbuch. Die Arbeiten des Jahres 2018 - Polz, Daniel; Wagner, Mareike (e-Forschungsberichte des DAI, 2018)
The coffins of Imeni and Geheset were found in Shaft K03.4, in Area H of the necropolis of Draʿ Abu el-Naga, in the north-eastern part of the Theban Necropolis, on the western bank of the Nile opposite the modern city of Luxor / Upper Egypt. Shaft K03.4 is dated to the 13th Dynasty and was discovered and excavated during the seasons of 2003 and 2004. During the course of the excavations, the burial of Geheset was discovered in a small chamber on the bottom of the shaft, where (the) two coffins were found in situ. The exterior coffin of Imeni is of very high quality and decorated on the outside and inside whereas the interior coffin of Geheset is of poorer quality and only decorated on the outside. The most interesting and outstanding fact in connection with these coffins is that the coffin of Imeni seems to be one of the first artefacts known to date that is inscribed with chapters of the famous Book of the Dead.